Are Effect Sizes in Emotional Intelligence Field Declining? A Meta-Meta Analysis - Gong, Zhun; Jiao, Xinian (Frontiers in Psychology, 2019)
Since Mayer and Salovey (1990) first proposed the emotional intelligence (EI) as an independent intellectual component, research on the field of EI has developed rapidly. A large number of studies have shown that emotional intelligence is an important predictor that affects our lives, such as job performance, mental health, and so on. However, we observed that some effect sizes in the field of emotional intelligence decreased over time. Is this kind of decline simply due to random errors, or is emotional intelligence field undergoing decline effects? The present study analyzed 484 effect sizes based on the responses of 102579 participants from nine meta-analyses in emotional intelligence field to estimate the average effect size, and evidence for decline effects in this field. This study finds that the average effect size of EI is 0.244 (p<0.001), and the average effect size of mixed EI (r=0.272, p<0.001) is significantly higher than that of ability EI (r=0.160, p<0.001). Effect sizes in the field of EI decrease with time, there are decline effects in emotional intelligence field. Furthermore, there are also decline effects in mixed EI field. However, we find no evidence that there are decline effects in ability EI field. Base on the significant average effect size of mixed EI, the most likely explanation for the decline in effect sizes is that effect sizes of mixed EI in the original studies were overestimate. This study considers decline effects in mixed EI research as inflated decline effects. To sum up, decline effects in the field of emotional intelligence are mainly due to the choice of emotional intelligence model and measurement method.